Oral ixazomib maintenance following autologous stem cell transplantation (TOURMALINE-MM3): a double-blind, randomised, placebo-controlled phase 3 trial - Dimopoulos, Meletios A.; Goldschmidt, Hartmut (The lancet, 2019)
Summary. Background Maintenance therapy following autologous stem cell transplantation (ASCT) can delay disease progression and prolong survival in patients with multiple myeloma. Ixazomib is ideally suited for maintenance therapy given its convenient once-weekly oral dosing and low toxicity profile. In this study, we aimed to determine the safety and efficacy of ixazomib as maintenance therapy following ASCT. Methods The phase 3, double-blind, placebo-controlled TOURMALINE-MM3 study took place in 167 clinical or hospital sites in 30 countries in Europe, the Middle East, Africa, Asia, and North and South America. Eligible participants were adults with a confirmed diagnosis of symptomatic multiple myeloma according to International Myeloma Working Group criteria who had achieved at least a partial response after undergoing standard-of-care induction therapy followed by high-dose melphalan (200 mg/m2) conditioning and single ASCT within 12 months of diagnosis. Patients were randomly assigned in a 3:2 ratio to oral ixazomib or matching placebo on days 1, 8, and 15 in 28-day cycles for 2 years following induction, high-dose therapy, and transplantation. The initial 3 mg dose was increased to 4 mg from cycle 5 if tolerated during cycles 1-4. Randomisation was stratified by induction regimen, pre-induction disease stage, and response post-transplantation. The primary endpoint was progression-free survival (PFS) by intention-to-treat analysis. Safety was assessed in all patients who received at least one dose of ixazomib or placebo, according to treatment actually received. This trial is registered with ClinicalTrials.gov, number NCT02181413, and follow-up is ongoing. Findings Between July 31, 2014, and March 14, 2016, 656 patients were enrolled and randomly assigned to receive ixazomib maintenance therapy (n=395) or placebo (n=261). With a median follow-up of 31 months (IQR 27·3-35·7), we observed a 28% reduction in the risk of progression or death with ixazomib versus placebo (median PFS 26·5 months [95% CI 23·7-33·8] vs 21·3 months [18·0-24·7]; hazard ratio 0·72, 95% CI 0·58-0·89; p=0·0023). No increase in second malignancies was noted with ixazomib therapy (12 [3%] patients) compared with placebo (eight [3%] patients) at the time of this analysis. 108 (27%) of 394 patients in the ixazomib group and 51 (20%) of 259 patients in the placebo group experienced serious adverse events. During the treatment period, one patient died in the ixazomib group and none died in the placebo group. Interpretation Ixazomib maintenance prolongs PFS and represents an additional option for post-transplant maintenance therapy in patients with newly diagnosed multiple myeloma. Funding Millennium Pharmaceuticals, a wholly owned subsidiary of Takeda Pharmaceutical Company.